EFICIÊNCIA DA LIMPEZA E DESINFECÇÃO DE COLCHÕES HOSPITALARES: CONTRIBUIÇÃO PARA SEGURANÇA DO PACIENTE - Ruberval Peres Gasques (2023)
Mattresses, often considered non-critical surfaces, can harbor harmful microorganisms due to direct contact with patients and exposure to bodily fluids, which makes them potential sources of infection. The high microbial load in these mattresses increases the risk of spreading pathogens between patients and healthcare professionals unless cleaning practices are effective. This study aims to analyze the effectiveness of cleaning and terminal disinfection practices for hospital mattresses, focusing on patient safety. The study adopted a cross-sectional and analytical approach conducted from October to December 2021 in a philanthropic hospital in the interior of the State of Mato Grosso do Sul, Brazil. The evaluation of the effectiveness of cleaning and disinfection of 40 mattresses used two monitoring methods: fluorescent marker, applied at six points before the cleaning and disinfection process, and microbiological culture, which involved counting colony forming units (CFU) at three points, both before and after the cleaning and disinfection process, carried out in three distinct areas of each mattress (top, middle and bottom). Overall, there was a statistically significant difference in the microbial count of mattresses after cleaning and terminal disinfection (p<0.001). There were no significant differences (p=0.050) when comparing the variation in microbial counts between the surgical and the clinical unit, indicating that the mattress cleaning and disinfection process was equally effective in both locations. Both in the global context (p<0.001) and specific collection areas (surgical unit; p=0.002 and clinical unit; p<0.001), there was a significant increase (p<0.05) in the proportion of approved areas— surfaces that had a microbial count of less than 60 CFU/cm2. Using this method, 36 (90%) mattresses were approved after cleaning and disinfection. Concerning the fluorescent marker, the results of the proportion test demonstrated that the number of mattress areas considered approved was significantly higher when compared to the areas that failed (p=0.022). Considering approval with the total removal of the marker, 17 (42.5%) mattresses were approved after cleaning and disinfection. Besides, no significant relationship was identified between the microbial counting and fluorescent marker methods (p=0.185). These results highlight the importance of rigorous cleaning and disinfection protocols for hospital mattresses to prevent the spread of pathogens and promote patient safety. The use of monitoring methods, such as fluorescent markers and microbiological analyses, can be essential to guarantee the effectiveness of these processes and reduce the risks of hospital infections. Therefore, these findings demonstrate direct implications for clinical practice, providing valuable guidance for improving the quality of care in hospital settings.